Clinicopathology of Immunoglobulin G4–Related Chronic Sclerosing Sialadenitis: A Single-Center Study. (December 2016) - Chang, Dun-Hao; Wu, Pao-Shu; Wang, Yu-Chen; Lin, Chin-Hsuan; Li, Wing-Yin; Ma, Hsu; Perng, Chern-Kang
Objectives: To investigate the clinicopathologic characteristics of patients with immunoglobulin G4–related chronic sclerosing sialadenitis (IgG4-RCSS), a recently recognized disease. Study Design: Case series with chart review and pathology study. Settings: Tertiary care hospital. Subjects and Methods: We evaluated chronic sialadenitis specimens obtained over 11 years using pathologic examination and IgG4 immunohistochemistry staining. The specimens were assigned a revised diagnosis of IgG4-RCSS or chronic sialadenitis not otherwise specified, and clinicopathologic data from each group were compared. Results: Of the 84 patients, 21 were diagnosed with IgG4-RCSS and 63 with chronic sialadenitis not otherwise specified. IgG4-RCSS patients were older (68.2 ± 13.9 vs 54.2 ± 15.8 years, P = .001), predominantly male (85.7% vs 61.9%, P = .036), and more likely to present with painless swelling (75% vs 44.3%, P = .001) and bilateral involvement (52.4% vs 6.3%, P < .001). Ratio of IgG4-positive plasma cells to IgG-positive plasma cells in IgG4-RCSS tissues was 0.81 ± 0.14. The mean value of serum IgG4 in IgG4-RCSS patients was 918.8 mg/dL. Conclusion: IgG4-RCSS is more common in older male patients and frequently presents with bilateral involvement. Informing head and neck surgeons of the clinical features of IgG4-RCSS and promoting a combined approach of clinical evaluation, imaging, and biopsy can improve the accuracy of preoperative diagnoses.